2019
DOI: 10.1007/978-3-030-16413-3
|View full text |Cite
|
Sign up to set email alerts
|

A Multidisciplinary Framework of Information Propagation Online

Abstract: the material is concerned, specifically the rights of translation, reprinting, reuse of illustrations, recitation, broadcasting, reproduction on microfilms or in any other physical way, and transmission or information storage and retrieval, electronic adaptation, computer software, or by similar or dissimilar methodology now known or hereafter developed. The use of general descriptive names, registered names, trademarks, service marks, etc. in this publication does not imply, even in the absence of a specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…Furthermore, social networking sites administrators should develop policies regarding the volume of information sharing ( Nawaz et al., 2018 ), particularly during crises. In the recent past, social bots and cyborg have been used to develop and steer public opinion in a particular direction ( Alsmadi & O'Brien, 2020 ; Zhang & Ghorbani, 2020 ), their use during a pandemic for causing panic cannot be diminished ( Paletz, Auxier, & Golonka, 2019 ). This area also needs special attention from the administrators of social networking sites.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, social networking sites administrators should develop policies regarding the volume of information sharing ( Nawaz et al., 2018 ), particularly during crises. In the recent past, social bots and cyborg have been used to develop and steer public opinion in a particular direction ( Alsmadi & O'Brien, 2020 ; Zhang & Ghorbani, 2020 ), their use during a pandemic for causing panic cannot be diminished ( Paletz, Auxier, & Golonka, 2019 ). This area also needs special attention from the administrators of social networking sites.…”
Section: Discussionmentioning
confidence: 99%
“…Companies' marketing activities (online news, web sites) are considered as a proxy for marketer-generated content (MGC), while consumers' online activities (blog posts and search traffic representing consumers' interest in new products) are considered user-generated content (UGC). The latter is treated as a tool to promote product information, as consumers' demand is highly sensitive to the data volumes of UGC shared on-line by potential consumers with informational utility (Paletz et al, 2019;Kim & Hanssens, 2017;Riz, 2013;Di Pietro & Pantano, 2012;Taylor et al, 2012). Paletz et al (2019) and Kim and Hanssens (2017) demonstrated that the UGC had more influence on demand than did firms' marketing activities, however, firms' marketing activities promote consumers' interests by increasing the chance of exposure to products.…”
Section: Methods and Data Collectionmentioning
confidence: 99%
“…The latter is treated as a tool to promote product information, as consumers' demand is highly sensitive to the data volumes of UGC shared on-line by potential consumers with informational utility (Paletz et al, 2019;Kim & Hanssens, 2017;Riz, 2013;Di Pietro & Pantano, 2012;Taylor et al, 2012). Paletz et al (2019) and Kim and Hanssens (2017) demonstrated that the UGC had more influence on demand than did firms' marketing activities, however, firms' marketing activities promote consumers' interests by increasing the chance of exposure to products. In order to check which type of on-line marketing activities is more beneficial for improving prediction accuracy, the second hypothesis was formulated:…”
Section: Methods and Data Collectionmentioning
confidence: 99%
“…The categories were selected to cover a wide definition of content associated with false information. They were developed based on terminology used in previous research [3,4,8,9,23,48,52], while also keeping in mind the less formal communication style on Reddit (hence the sixth category). The exact terms used for each category can be inspected at the end of Appendix B.…”
Section: Keyword Filteringmentioning
confidence: 99%
“…Finally, the "authors" tab shows the most flagged users (as percent of total submisions). This can be useful to detect potential coordinated activity by groups of non-genuine users [52], social bots, or trolls that might stand out for having an unusually high number of flagged comments.…”
Section: Dashboard: Subreddits Domains Authorsmentioning
confidence: 99%